PENDEKATAN DEEP LEARNING MENGGUNAKAN METODE LSTM UNTUK PREDIKSI HARGA BITCOIN - Hastari Utama (Hemispheres Press, 2023)
Bitcoin price prediction involves analyzing a variety of factors, including market sentiment, trading volume, economic news, technological developments, and other factors that affect supply and demand. Both technical and fundamental analysis methods can be used to try to predict Bitcoin price movements. In this Bitcoin price prediction using a Deep Learning approach with the chosen method is LSTM. The LSTM (Long Short-Term Memory) method is a popular type of Recurrent Neural Network (RNN) model for predicting the price of Bitcoin and other financial assets. LSTM can solve the problem of price movements that have long-term dependencies, which traditional RNN models cannot handle well. LSTMs have the ability to